2019
DOI: 10.13044/j.sdewes.d7.0271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Agricultural Practices on Carbon Emission and Soil Health

Abstract: The agricultural sector is a source of greenhouse gas emissions that directly affect the global problem of climate change and contribute approximately 11% in total greenhouse gas emissions in the world and in Croatia too. Irregular and irresponsible agricultural practices, such as excessive tillage and improper fertilization often lead to soil carbon loss and increased carbon dioxide emissions to the atmosphere. This field study provides results how agricultural practices affect carbon dioxide emissions from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…Carbon dioxide emissions were higher from SCM compared with IF in all years. Similar to our results, other studies have shown that CO 2 emissions are greater from plots with manure fertilizers when compared to plots with inorganic fertilizers (Galic et al., 2019; Mapanda et al., 2011). These higher CO 2 emissions with the use of organic fertilizers can be attributed to greater OM availability for microbial respiration in soil.…”
Section: Discussionsupporting
confidence: 92%
“…Carbon dioxide emissions were higher from SCM compared with IF in all years. Similar to our results, other studies have shown that CO 2 emissions are greater from plots with manure fertilizers when compared to plots with inorganic fertilizers (Galic et al., 2019; Mapanda et al., 2011). These higher CO 2 emissions with the use of organic fertilizers can be attributed to greater OM availability for microbial respiration in soil.…”
Section: Discussionsupporting
confidence: 92%
“…Application of municipal solid waste compost increased soil microbial populations. Our results corroborate those of Galic et al [13] who carried out a long-term fertilization study on the growing season of wheat and maize and finally concluded that the highest CO2 flux in the soil came from the treatment of organic fertilizers. Also Alate et al [14] in a study carried out in Togo on CO2 emissions from the soil in a tomato test field subjected to different water regimes and doses of compost recorded the highest CO2 emissions on plots amended with compost.…”
Section: Respiration Of Soil Microbial Florasupporting
confidence: 91%
“…Meanwhile, nitrogen oxides and carbon dioxide are the main contributors to the negative impact on the environment [111], which are generated in irregular and irresponsible agricultural practices [112], electricity generation [113], and transportation [114]. Researchers focused on the combustion processes of conventional solid and liquid fuels with inorganic or biomass additive to reduce pollutant emission [115]. Another effective method for achieving pollutant emission reduction is the application of CO 2 carbon management technologies, including CO 2 capture and storage, which is a competitive solution to mitigate global warming [116].…”
Section: Power Plant and Electric Systemsmentioning
confidence: 99%